Acknowledgement to Reviewers of Journal of Functional Biomaterials in 2017 - Journal of Functional Biomaterials Editorial Office (Journal of Functional Biomaterials, 2018)
Peer review is an essential part in the publication process, ensuring that Journal of Functional Biomaterials maintains high quality standards for its published papers[...]